2021
DOI: 10.3390/cancers13071703
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 2 Isoforms Detected via Novel RNA ISH as Predictive Biomarkers for Progestin Therapy in Atypical Hyperplasia and Low-Grade Endometrial Cancer

Abstract: Women with atypical hyperplasia (AH) or well-differentiated early-stage endometrioid endometrial carcinoma (EEC) who wish to retain fertility and/or with comorbidities precluding surgery, are treated with progestin. Clinically approved predictive biomarkers for progestin therapy remain an unmet need. The objectives of this study were to document the overall response rate (ORR) of levonorgestrel intrauterine device (LNG-IUD) treatment, and determine the association of FGFR2b and FGFR2c expression with treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previously, we reported that the expression of FGFR2c splice isoform was associated with aggressive tumor characteristics and poor survival outcome [ 11 ] as well as progestin treatment failure in a separate cohort of women [ 20 ]. In this former study, tumors with expression of FGFR2c were compared to all those not expressing FGFR2c (including those that had lost both FGFR2b and FGFR2c expression) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that the expression of FGFR2c splice isoform was associated with aggressive tumor characteristics and poor survival outcome [ 11 ] as well as progestin treatment failure in a separate cohort of women [ 20 ]. In this former study, tumors with expression of FGFR2c were compared to all those not expressing FGFR2c (including those that had lost both FGFR2b and FGFR2c expression) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We employed the BaseScope RNA ISH assay that has been previously developed, optimized, and validated by our laboratory to detect the FGFR2b and FGFR2c isoforms [ 11 , 20 ]. In brief, we utilized custom‐designed probes from Advanced Cell Diagnostic (ACD) (Newark, CA, USA): (1) a human‐specific probe (1ZZ) (BA‐Hs‐FGFR2‐tv2‐E7E8) that targets an exon 7–8 junction (NM_022970.3, 1,578–1,622 bp) to detect the ‘FGFR2b’ epithelial isoform and (2) a human‐specific probe (BA‐Hs‐FGFR2‐tv1‐E7E9) that targets an exon 7–9 junction (NM_000141.4, 1,580–1,619 bp) to detect the ‘ FGFR2c mRNA’ mesenchymal isoform.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial carcinoma is the most common gynecological malignancy, and EH is its precursor [ 1 ]. There is a strong relationship between the renin–angiotensin system and AngII receptors’ overexpression, and initiation and progression of EH and EC.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperplastic changes originate from the uterine endometrial glands with an increase in the gland-to-stroma ratio compared with the regular endometrium. Unfortunately, about 40% of EH patients with atypia develop carcinoma, the most common fatal gynecological malignancy [ 1 ]. The revised 2014 WHO classification divides EH into two categories: (1) hyperplasia without atypia and (2) atypical hyperplasia, based upon the presence or absence of cytological atypia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that abnormal mismatch repair (MMR) protein expression can predict poor response to progestins and/or higher rate of recurrence in young women with AH or FIGO 1 carcinoma ( 51 ). Finally, other authors reported that another biomarker, FGFR2c, appears to be strongly associated with progestin treatment failure, with low overall response rate to levonorgestrel intrauterine device treatment ( 52 ).…”
Section: Endometrial Carcinomamentioning
confidence: 99%